answersLogoWhite

0

First convert everything to sines and cosines:

sin x + sin x cos x / sin x = 1 / sin x

sin x + cos x = 1 / sin x

Multiplying by sin x:

sin2x + sin x cos x = 1

Using the identity sin2 + cos2x = 1:

sin2x + sin x cos x = sin2x + cos2x

sin x cos x = cos2x

Dividing by cos x:

sin x = cos x

The solution is therefore x = pi / 4 radians, or x = 5 pi / 4 radians.

The division by cos x assumed that cos x was not equal to zero; this possibility must be explored in the original equation. When cos x = 0, sin x = 1 or -1, and the angle x = pi/2 or -pi/2. It seems both of these are solutions, too.

First convert everything to sines and cosines:

sin x + sin x cos x / sin x = 1 / sin x

sin x + cos x = 1 / sin x

Multiplying by sin x:

sin2x + sin x cos x = 1

Using the identity sin2 + cos2x = 1:

sin2x + sin x cos x = sin2x + cos2x

sin x cos x = cos2x

Dividing by cos x:

sin x = cos x

The solution is therefore x = pi / 4 radians, or x = 5 pi / 4 radians.

The division by cos x assumed that cos x was not equal to zero; this possibility must be explored in the original equation. When cos x = 0, sin x = 1 or -1, and the angle x = pi/2 or -pi/2. It seems both of these are solutions, too.

First convert everything to sines and cosines:

sin x + sin x cos x / sin x = 1 / sin x

sin x + cos x = 1 / sin x

Multiplying by sin x:

sin2x + sin x cos x = 1

Using the identity sin2 + cos2x = 1:

sin2x + sin x cos x = sin2x + cos2x

sin x cos x = cos2x

Dividing by cos x:

sin x = cos x

The solution is therefore x = pi / 4 radians, or x = 5 pi / 4 radians.

The division by cos x assumed that cos x was not equal to zero; this possibility must be explored in the original equation. When cos x = 0, sin x = 1 or -1, and the angle x = pi/2 or -pi/2. It seems both of these are solutions, too.

First convert everything to sines and cosines:

sin x + sin x cos x / sin x = 1 / sin x

sin x + cos x = 1 / sin x

Multiplying by sin x:

sin2x + sin x cos x = 1

Using the identity sin2 + cos2x = 1:

sin2x + sin x cos x = sin2x + cos2x

sin x cos x = cos2x

Dividing by cos x:

sin x = cos x

The solution is therefore x = pi / 4 radians, or x = 5 pi / 4 radians.

The division by cos x assumed that cos x was not equal to zero; this possibility must be explored in the original equation. When cos x = 0, sin x = 1 or -1, and the angle x = pi/2 or -pi/2. It seems both of these are solutions, too.

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

BlakeBlake
As your older brother, I've been where you are—maybe not exactly, but close enough.
Chat with Blake
BeauBeau
You're doing better than you think!
Chat with Beau
JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
More answers

First convert everything to sines and cosines:

sin x + sin x cos x / sin x = 1 / sin x

sin x + cos x = 1 / sin x

Multiplying by sin x:

sin2x + sin x cos x = 1

Using the identity sin2 + cos2x = 1:

sin2x + sin x cos x = sin2x + cos2x

sin x cos x = cos2x

Dividing by cos x:

sin x = cos x

The solution is therefore x = pi / 4 radians, or x = 5 pi / 4 radians.

The division by cos x assumed that cos x was not equal to zero; this possibility must be explored in the original equation. When cos x = 0, sin x = 1 or -1, and the angle x = pi/2 or -pi/2. It seems both of these are solutions, too.

User Avatar

Wiki User

15y ago
User Avatar

Add your answer:

Earn +20 pts
Q: Simplify sin x plus sin x cotx equals cscx?
Write your answer...
Submit
Still have questions?
magnify glass
imp